Facile oxidation of flavanones to flavones using [hydroxy(tosyloxy)iodo]benzene in an ionic liquid - Muthukrishnan, Murugan; Patil, P. S.; More, Shivaji V.; Joshi, Ramesh A. (Mendeleev Communications, 2005)
A method for the oxidation of flavationes to flavones has been developed using [hydroxy(tosyloxy)iodo] benzene (HTIB) in the room-temperature ionic liquid 1,3-di-n-butylimidazolium bromide ([bbim]Br-+(-)).

First ionic liquid-promoted Kabbe condensation reaction for an expeditious synthesis of privileged bis-spirochromanone scaffolds - Muthukrishnan, Murugan; Basavanag, U. M. V.; Puranik, Vedavati G. (Tetrahedron Letters, 2009)
A variety of privileged bis-spirochromanones were synthesized for the First time from 4,6-diacetyl resorcinol in one-pot by carrying out the Kabbe condensation in loom temperature ionic liquid [bbim]Br. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bis-spirochromanone; Ionic liquid; Kabbe condensation; Morpholine

Facile enantioselective synthesis of enantiomerically pure (R)-phenoxybenzamine hydrochloride using the hydrolytic kinetic resolution method - Nikalje, Milind D.; Sasikumar, Murugesan; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2010)
A practical and highly efficient enantioselective synthesis of (R)-phenoxybenzamine hydrochloride has been described for the first time using Jacobsen's hydrolytic kinetic resolution of a terminal epoxide as a key step and source of chirality. (C) 2010 Elsevier Ltd. All rights reserved.

First asymmetric synthesis of the antiepileptic drug lacosamide (Vimpat (R)) based on a hydrolytic kinetic resolution strategy - Muthukrishnan, Murugan; Mujahid, Mohammad; Sasikumar, M.; Mujumdar, P. (Tetrahedron-Asymmetry, 2011)
An efficient asymmetric synthesis of the new antiepileptic drug, Lacosamide is described in high enantiopurity (>98% ee), using Jacobsen's hydrolytic kinetic resolution strategy as a key step. (C) 2011 Elsevier Ltd. All rights reserved.